2022
DOI: 10.55563/clinexprheumatol/sian1b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality of life in Behçet's disease: a systematic review

Abstract: Objective. The assessment of quality of life (QoL) in Behçet's disease (BD) patients has been a surrogate of disease outcomes, but a wider impact on the patient's lifestyle has not been considered. This systematic review aims to provide an overview of the existing tools specifically adopted to explore the QoL in BD patients. Methods. A systematic literature review was conducted using 2 electronic databases, according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Avoiding triggers, whenever known, can also help prevent flare-ups. Regular dental hygiene can help avoid oral ulcers, and protection from sun and heat might help prevent skin lesions [75,76]. Regular followup with healthcare providers ensures appropriate management and prompt treatment of flare-ups [77][78][79][80].…”
Section: What Lifestyle Modifications Can Help Manage Behçet's Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding triggers, whenever known, can also help prevent flare-ups. Regular dental hygiene can help avoid oral ulcers, and protection from sun and heat might help prevent skin lesions [75,76]. Regular followup with healthcare providers ensures appropriate management and prompt treatment of flare-ups [77][78][79][80].…”
Section: What Lifestyle Modifications Can Help Manage Behçet's Disease?mentioning
confidence: 99%
“…The chronic and potentially disabling nature of Behçet's disease also brings pain specialists and mental health professionals to the fore, providing much-needed pain and psychological support [73]. Nurses, physical therapists, and patient educators are integral members of the care team, also in keeping a watchful eye on the patient's overall status, including any side effects from the medication [76].…”
Section: While a Multidisciplinary Approach Is Required For Behçet's ...mentioning
confidence: 99%
“…Studies have shown the significant impact of BD on the quality of life and life satisfaction of patients [20][21][22][23][24][25]. Patients' quality of life and perceptions of wellness are becoming increasingly acknowledged as end points and targeted outcomes in studies Li & Yacyshyn JMIR FORMATIVE RESEARCH XSL • FO RenderX [26]. The illness perception of patients can also play a significant role in the relationship between symptom severity and perceived pain or energy level [27].…”
Section: Principal Findingsmentioning
confidence: 99%
“…anxiety occur more frequently in BS patients than in the general population (80)(81)(82). Young patients and those with low socio-economic status are more severely affected (80).…”
Section: Clinical and Experimental Rheumatology 2023mentioning
confidence: 99%